Thermal Stability of Self-Assembled Monolayers of n-Hexanethiol on Au(111)-(1 × 1) and Au(001)-(1 × 1) - Cristina, Lucila Josefina (2017)
Thermal desorption in an ultrahigh vacuum of n-hexanethiol (C6T) self-assembled monolayers (SAMs) prepared from ethanolic solutions on Au(111) and Au(001) unreconstructed surfaces was investigated by X-ray photoelectron spectroscopy. The SAMs desorption was performed from room temperature (RT) to 380 K. We report that the hexanethiolate surface saturation coverage is bigger (∼0.4 ML) for the SAM on Au(001) than on Au(111) (∼0.33 ML). We identified a greater stability for C6T SAMs on Au(001). Large amounts of physisorbed species were found on preferred oriented (111) polycrystalline Au at the low coverage regime at RT, while the SAM on the Au(001) single crystal at this conditions desorbs at a steady pace. At 340 K, both SAMs remain stable at the coverage expected for the lying-down phases that maximizes the van der Waals interactions. We observe that at higher temperatures the carbon alpha-sulfur bond breaks, producing free S on both gold surfaces.